Understanding Fast and Slow Unrest at Volcanoes and Implications for Eruption Forecasting - Stix, John (Frontiers in Earth Science, 2018)
This paper examines the behavior of volcanoes that erupt quickly with paroxysmal explosive eruptions, and other volcanoes that erupt over extended periods without such paroxysmal activity. “Fast” activity typically occurs over the course of months to years, including precursory unrest, the paroxysmal eruption itself, and post-paroxysmal activity. “Slow” activity comprises extended restlessness over the course of decades, and eruptions are typically small and sometimes uncommon. I review activity at eight volcanoes with fast and slow activity, highlighting the main events, and commonalities in behavior among the different systems. In terms of forecasting, volcanoes with fast unrest typically have short 1–3 month precursory periods prior to the climactic eruption, while volcanoes with slow unrest commonly have an extended period of considerable uncertainty regarding the presence or absence of new magma, as well as unanticipated accelerations in activity. Volcanoes with fast behavior are associated with magmas having elevated volatile contents (up to 7 wt. % H2O), rapid magma ascent rates, and rapid declines in activity after the climactic eruption. These volcanoes also exhibit well-defined magma plumbing systems containing mobile volatile-rich magma, with the plumbing system often sealed between the top of the shallow magma reservoir and the surface prior to the climactic eruption. Volcanoes with slow behavior have complex plumbing systems comprising cracks, fractures, dykes, and sills and magmas that are crystal-rich, partly degassed, and rheologically sluggish. These volcanoes experience a progressive opening of their systems as magma intrudes and fractures country rock, allowing degassing to occur. The degree to which a system is opened is determined by the rate at which new magma is emplaced at shallow levels. As such, magma emplacement rates which are fast, intermediate, or slow should produce unrest on similar timescales. Slower rates of emplacement enhance the opening process due to a cumulatively high number of fractures and increased fracture density which develop during the extended period of unrest. Many systems both fast and slow receive inputs of more mafic magma which can drive activity seen at the surface. A series of recently developed tools is examined and discussed in order to provide an improved means of forecasting activity at both types of volcanoes. These include assessment of early phreatic activity and associated gases, Vp/Vs ratios of magma by seismic tomography, and estimates of magma volume from precursory seismicity. What is required now are protocols which integrate these approaches in a manner which is useful for accurate forecasting.